Careers and Intergenerational Income Mobility - Catherine Haeck; Jean-William Laliberté (Institute of Labor Economics (IZA), 2023)
This paper uses Census microdata linked with tax records to quantify the contribution of career choices - occupations and fields of study - to intergenerational income mobility. We document substantial segregation into occupations by parental income. Yet, the occupations children pursue explain only a third of the intergenerational persistence of income. We further describe patterns of intergenerational occupational following and show they vary substantially across occupations, with low-paying occupations showing more persistence across generations on average. However, clustering into occupations based on parental income is mostly independent of parental occupations. Our results demonstrate that occupational persistence only weakly contributes to income immobility.
Keywords: J62; J24; 330; intergenerational mobility; occupational choice; income inequality